A survey on the unused and expired medication returned by patients at Out-patient Department (OPD) in Hospital Universiti Sains Malaysia (HUSM) - Mohd Fauzi, Nur Fatini; Sahumi, Nur Syazlin; Saberi, Siti Mariana Anis (2018)
A medication take-back event in hospital pharmacy is very appropriate. It is because a few previous research conducted by authorities had revealed that many of the medication returned by consumers (patients) are able to be reuse. This research is conducted to explore the reasons why patients returned their medicines at the pharmacy counter in Out Patient Department (OPD), Hospital Universiti Sains Malaysia under Kempen Pemulangan Semula Ubat-ubatan. During returning the medicines, the patients who fulfill the inclusion criteria will be approached by investigators. The main focus of this survey was to identify on the reasons why the patients returned the unused and expired medications at Out Patient Department (OPD) in Hospital Universiti Sains Malaysia (HUSM). Another focus of this survey was to examine the relationship between the level of education and ways of disposing of the medicines by respondents. From this research, we manage to collect 120 surveys and key in the data into SPSS version 23.0 software to get the result in table form and also graph form. The result of the research will help the government and hospital to improve the awareness on drug disposal and drug compliance.